A method to couple state-based peridynamics and finite element method for crack propagation problem. (January 2019) - Fang, Guodong; Liu, Shuo; Fu, Maoqing; Wang, Bing; Wu, Zengwen; Liang, Jun
Highlights: A coupled finite element and state-based peridynamic method is proposed. The coupling method can greatly improve the computation efficiency compared with PD. The coupling model is high accurate to analyze the 2D crack propagation problem. Abstract: A coupling method of the state-based Peridynamics and the finite element method (FEM) is proposed here to solve the problem of crack propagation. It has both the advantage of Peridynamics in solving discontinuous problems and the computational efficiency of FEM. The solution domain is partitioned into three regions: Peridynamic region, FEM region and coupling region. Crack propagation happens in the Peridynamic region. The remaining region is discretized by FEM. The coupling method is achieved in the following way: the Peridynamic particle is connected non-locally to all particles, i.e., Peridynamic particles and finite element nodes within its horizon, and the finite element node applies force upon all nodes around it. The accuracy and efficiency of the proposed method are verified in solving crack propagation problems.